Antioxidant and gastric cytoprotective prostaglandins properties of Cassia sieberiana roots bark extract as an anti-ulcerogenic agent - Nartey Edmund T; Ofosuhene Mark; Kudzi William; Agbale Caleb M (BMC, 2012)
Abstract Background Cassia sieberiana is a savannah tree with a wide phytotherapeutic application including the use of its roots in the management of various stomach disorders including gastric ulcer, stomach pains and indigestion. The aim of the study is to evaluate the antioxidant, gastric cytoprotective prostaglandins, secretory phospholipase A2, phytochemical and acute toxicity properties of Cassia sieberiana roots bark extract in a bid to justify its phytotherapeutic applications in gastric ulcer. Methods Antioxidant and radical scavenging activities of the roots bark extract of Cassia sieberiana were assayed. Serum secretory phospholipase A2 (sPLA2) concentration and activity and the formation of gastric mucosal prostaglandins E2 (PGE2) and I2 (PGI2) were also assessed. Comparisons between means were performed using analysis of variance (ANOVA) followed by Students Standard Newman-Keuls post hoc analysis to determine statistical significance. P < 0.05 was considered significant. Results The extract was found to possess significant ferric reducing antioxidant power and can scavenge hydroxyl radicals. The extract also possesses DPPH scavenging activity, can chelate ferrous ion and a dose-dependent protective effect against lipid peroxidation and free radical generation. Prostaglandin studies showed that the roots bark extract dose dependently increased gastric mucosal PGE2 and PGI2 levels and also decreased serum sPLA2 activity. Phytochemical analyses suggest that the roots extract contains polyhydroxyl/phenolic substances. Acute toxicity test showed no sign of toxicity up to a dose level of 2000 mg/kg body weight p.o. Conclusions C. sieberiana roots extract possesses significant antioxidant and gastric cytoprotective prostaglandin properties as well as serum secretory phospholipase A2 inhibitory activity which could be due to its content of polyhydroxy and/or phenolic substances. This may justify its use as an anti-ulcerogenic agent in traditional medicine in West Africa.